The Effectiveness of RAFT Strategy Combined with Process Writing Approach in Teaching Writing for Junior High School Students - Nurlia, Ratna; Ardini , Dessy Ayu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
This study aimed to determine the impact of the Role Audience Format Topic (RAFT) strategy combined with process writing approach on students' writing achievement. A quasi-experimental, non-randomized pre-test post-test design was employed, involving second-year junior high school students. Class 8A served as the experimental group, while Class 8B was the control group. A pre-test was administered to both groups before the treatment. The experimental group received instruction using the RAFT strategy, while the control group was taught using the grammar translation method. An analysis of covariance (ANCOVA) revealed a significant difference between the two groups. The p-value of .000, which is less than .05, indicates that students who were taught using the RAFT strategy achieved significantly better writing skills than those who were taught using the grammar translation method.